Theoretical studies of molecular structure and vibrational spectra of 2-amino-5-phenyl-1,3,4-thiadiazole - Atalay, Y; Yakuphanoglu, E; Sekerci, M; Avci, D; Basoglu, A (Pergamon-Elsevier Science Ltd, 2006)
The molecular geometry and vibrational frequencies of 2-amino-5-phenyl-1,3,4-thiadiazole (C8H7N3S) in the ground state has been calculated using the Hartree-Fock and density functional method (B3LYP) with 6-31G(d) basis set. The optimized geometric bond lengths and bond angles obtained by using HF and DFT (B3LYP) show the best agreement with the experimental data. Comparison of the observed fundamental vibrational frequencies of 2-amino-5-phenyl-1,3,4-thiadiazole (C8H7N3S) and calculated results by density functional B3LYP and Hartree-Fock methods indicate that B3LYP is superior to the scaled Hartree-Fock approach for molecular vibrational problems. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-amino-5-phenyl-1,3,4-thiadiazole; IR spectra; DFT; HF; vibrational assignment; crystal structure